Detection rate of fluorine-18 prostate-specific membrane antigen-1007 PET/CT for prostate cancer in primary staging and biochemical recurrence with different serum PSA levels: A systematic review and meta-analysis - Liu, Xue; Jiang, Tao; Gao, CaiLiang; Liu, HuiTing; Sun, Yu; Zou, Qiao; Tang, Rui; Zeng, WenBing (Frontiers in Oncology, 2022)
Background: We performed a systematic review and meta-analysis to evaluate the detection rate (DR) of fluoro-prostate specific membrane antigen (18F-PSMA-1007) PET/CT in patients with different serum prostate specific antigen (PSA) levels in the setting of primary staging of prostate cancer (PCa) or biochemically recurring PCa. Methods: A comprehensive electronic literature search of the PubMed, Embase and Cochrane Library databases were conducted in accordance with the PRISMA statement. This study was registered in the PROSPERO database (registration number: CRD42022331595). We calculated the DR of 18F-PSMA-1007 PET/CT in PCa. Results: The final analysis included 15 studies that described 1022 patients and 2034 lesions with 18F-PSMA-1007 PET/CT in PCa. The DR of 18F-PSMA-1007 PET/CT in patient with PCa in primary staging ranged from 90% to 100%, with a pooled estimate of 94% (95%CI: 92%-96%). The DR of 18F-PSMA-1007 PET/CT in patient with PCa in BCR ranged from 47% to 100%, with a pooled estimate of 86% (95%CI: 76%-95%). The DR of PSA levels >2.0, 1.1–2.0, 0.51–1.0 and ≤0.5ng/mL detected by 18F-PSMA-1007 PET/CT in a patient-based analysis were 97% (95%CI:93%-99%), 95% (95%CI:88%-99%), 79% (95%CI:68%-88%), and 68% (95%CI:58%-78%), respectively. Conclusion: This meta-analysis concluded that 18F-PSMA-1007 PET/CT had a high application value for prostate cancer, including primary tumors and biochemical recurrence. The DR of 18F-PSMA-1007 PET/CT was slightly higher in primary prostate tumor than biochemical recurrence.